2014
DOI: 10.1097/qai.0000000000000220
|View full text |Cite
|
Sign up to set email alerts
|

The Montreal Cognitive Assessment to Screen for Cognitive Impairment in HIV Patients Older Than 60 Years

Abstract: Progress in HIV treatments has led to HIV-infected patients living into their 60s and older. Since HIV-associated Neurocognitive Disorder (HAND) in older age is associated with more executive dysfunction, cognitive screening instruments tapping this domain may be optimal. We examined the Montreal Cognitive Assessment (MoCA) to identify HAND in 67 HIV-infected patients over age 60, of which 40% were diagnosed with HAND. Receiver operator characteristics (ROC) curve identified an optimized cut-off ≤25/30 identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 26 publications
1
45
4
Order By: Relevance
“…We found a cut-off of ≤26 as the most optimal balance of sensitivity and specificity, which is somewhat higher than the ≤25 cut-point found in other studies in HIV (Chartier et al, 2015; Hasbun et al, 2012; Janssen et al, 2015; Ku et al, 2014; Milanini et al, 2014; Overton et al, 2013). Moreover, the optimal MoCA cut-off remained the same when participants with significant confounding neuromedical factors (e.g., history of stroke, severe head injury) were excluded from analyses.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…We found a cut-off of ≤26 as the most optimal balance of sensitivity and specificity, which is somewhat higher than the ≤25 cut-point found in other studies in HIV (Chartier et al, 2015; Hasbun et al, 2012; Janssen et al, 2015; Ku et al, 2014; Milanini et al, 2014; Overton et al, 2013). Moreover, the optimal MoCA cut-off remained the same when participants with significant confounding neuromedical factors (e.g., history of stroke, severe head injury) were excluded from analyses.…”
Section: Discussioncontrasting
confidence: 73%
“…Some studies converge to support the MoCA as a practical and valid neurocognitive screening tool in HIV+ adults (Brouillette et al, 2015; Chartier et al, 2015; Hasbun et al, 2012; Koski et al, 2011; Ku et al, 2014; Overton et al, 2013; Robbins et al, 2013; Valcour, 2011), although not sufficient as a stand-alone tool for diagnosing HAND (Chartier et al, 2015; Janssen, Bosch, Koopmans, & Kessels, 2015). To our knowledge, only one study has examined the MoCA as a neurocognitive screener in older HIV+ adults and found the MoCA moderately sensitive and specific for HIV+ adults aged 60 and older, yielding 72% sensitivity and 67% specificity with a cut-off of ≤25 (Milanini et al, 2014). However, the utility of the MoCA in predicting real-world outcomes important for treatment planning is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive impairment was found in 30% of breast cancer patients prior to chemotherapy and 35% many years after treatment [26] . Similar studies utilizing the MoCA found 40% of patients with HIV [27] and 45% with a history of stroke [28] had MCI.…”
Section: Discussionmentioning
confidence: 70%
“…The MoCA is highly sensitive and may overestimate MCI at the recommended normal range (score of [26][27][28][29][30], particularly in participants with lower levels of education [48] . Although we did not collect a detailed history of education, this is partially offset in scoring the MoCA by adding 1 point for participants with ≤ 12 years of formal education.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several other studies, including one recruiting only participants aged >60 years and one using a locally modified version in Korea, have also reported lower sensitivity but higher specificity. [111][112][113] Thus, there is a wide range of diagnostic accuracy estimates for the MoCA, similar to the HDS and IHDS. In all studies, the LR+ is <5 and the LR-is >0.2, implying that the test is limited in its diagnostic power.…”
mentioning
confidence: 99%